0307 Monitoring Mercury Exposure Among Artisanal and Small-Scale Miners: Developing and Evaluating a Surveillance Protocol. (23rd June 2014) - Gracia, Gabriela; Forst, Linda
Abstract : Objectives: - Develop a mercury exposure surveillance protocol targeted at artisan and small-scale miners that includes taking occupational histories, ancillary tests, counselling and educating patients regarding exposure - Obtain physician, subject matter and end user feedback on the protocol content and implementation feasibility - Develop a training guide for physicians and educational materials for miners - Pilot test the surveillance protocol among a small group of artisan miners Method: The Minamata Conference on Mercury highlighted the importance of surveillance protocols in identifying, treating and preventing mercury exposure among miners. As such, we will use materials from the World Health Organisation (WHO) and International Labour Organisation (ILO) to develop the protocol. We will collaborate with physicians, occupational health and small-scale mining experts to identify key content and obtain feedback regarding each section of the protocol. Once we have a finalised protocol, we will pilot test the protocol among a small group of artisan miners and incorporate lessons learned into the final product. Results: We will develop a surveillance protocol that will capture prevalence, occurrence, treatment and preventive efforts related to mercury exposure. The initial pilot testing will provide valuable feedback regarding the ease of use, content comprehension, effective treatment and preventive efforts associated with mercury exposure. Conclusions: Treating, preventing and reducing mercury exposure is a priority of the mining industry. In order to effectively reduce and eliminate mercury exposure it is important to develop an effective surveillance protocol tailored to artisan and small-scale miners.